Use calcium silicate filler to improve the properties of sago starch based degradable plastic - Rozanna Dewi; Novi Sylvia; Zulnazri Zulnazri; Medyan Riza; Januar Parlaungan Siregar; Tezara Cionita (AIMS Environmental Science)
The addition of fillers or additives to improve the mechanical properties of degradable plastics such as sago starch has gained the interest of researchers, scientists, and academicians. This research aims to investigate the addition of calcium silicate as an additive filler on the properties of a sago starch-based degradable plastic. The calcium silicate fillers used were 2, 4, 6, and 8% by weight starch, and the gelatinization process temperature used was 70, 80, and 90 ℃. The properties of these plastics were analyzed in terms of their strength, chemical composition, thermal stability, water absorption, and degradation rate. The optimum mechanical characteristics included a tensile strength of 28.04 MPa, 32.55 MPa of elongation at the break, and 70.02% of Young's modulus obtained with the addition of 8% calcium silicate and a gelatinization temperature of 90 ℃. Fourier Transform Infrared (FTIR) showed that there were O-H, C-H, and C = O groups that existed at wave numbers of 3795.91 cm-1, 2927.94 cm-1, and 1433.11–1616.35 cm-1; moreover, these groups are hydrophilic, which bind water, so they can be degraded by the microbial activity in the soil. Differential Scanning Calorimetry (DSC) showed that the degradable plastic had a thermogram peak at 271.38 ℃; additionally an endothermic peak occurred at 309.30 ℃. The maximum swelling value was 64.05% at 2% calcium silicate and a gelatinization temperature of 70 ℃. The addition of calcium silicate made the plastic more water-resistant. The degradation rate of the degradable plastic ranged from 12–15 days and conformed to the American Standard Testing and Materials (ASTM) D-20.96 (maximum 180 days of decomposition for degradable plastic).